Luminescent sensing and formation of mixed f-d metal ion complexes between a Eu(iii)-cyclen-phen conjugate and Cu(ii), Fe(ii), and Co(ii) in buffered aqueous solution - GUNNLAUGSSON, THORFINNUR (Royal Society of Chemistry, 2009)
The synthesis and photophysical properties of the Eu(III) complex 1.Eu, based on the use of 1,10-phenanthroline (phen) as a combined sensitizing antenna and a transition metal ion coordinating ligand, is described. The long-wavelength Eu(III) emission from this complex was found to be highly pH sensitive, giving rise to a off-on-off pH profile with maximum emission occurring within the physiological pH range. This allowed for the use of 1.Eu as a luminescent sensor for transition metal ions, where the titration with ions such as Cu(II), Co(II) and Fe(II) gave rise to the formation of mixed f?d nuclear complexes, with concomitant changes in the photophysical properties of 1.Eu. Here, changes in both the ground and the singlet excited state properties of the phen antenna were observed, but the largest changes were observed for the delayed Eu emission, which was fully quenched upon titration with these ions in aqueous pH 7.4 buffered solutions. In comparison, no changes were observed in the Eu(III) emission upon titration with ions such as Zn(II) or group I and II ions. From these changes, we were able to demonstrate the binding stoichiometry and the binding constant for the formation of novel supramolecular complexes between 1.Eu and Cu(II), Co(II) and Fe(II), which showed that either two or three equivalents of 1.Eu complexed to each of these transition metal ions, giving rise to the formation either linear f?d?f or branched f3?d based mixed nuclear complexes in solution.
PUBLISHED
Keywords: Chemistry